Model Pengembangan Bahan Ajar Tematik bagi Sekolah Dasar - Harinangsi Napu; Nurain Mohammad (Inovasi Pendidikan dan Anak Usia Dini, 2026)
This study discusses the development of thematic teaching materials in elementary schools to improve the quality of learning in accordance with the 2013 Curriculum. The research method used is research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results show that the thematic teaching materials developed with approaches such as Project Based Learning (PjBL), Problem Based Learning (PBL), and Contextual Teaching and Learning (CTL) can enhance students' critical thinking, creativity, and social responsibility skills. The integration of local wisdom values as well as the use of digital and contextual teaching materials make learning more engaging, interactive, and meaningful. The thematic teaching materials based on these innovative learning models can help students develop 21st-century skills. Thus, the development of thematic teaching materials based on innovative models is an effective strategy for creating quality learning in elementary schools that is relevant to curriculum demands and the needs of today's learners. The use of technology and contextual approaches enriches students' learning experiences, making them more relevant and beneficial in daily life.